APLIKASI TEKNIK RELAKSASI BENSON TERHADAP PENGELOLAAN TEKANAN DARAH DAN PSIKOLOGIS PADA LANSIA DENGAN HIPERTENSI - Ramadhani, Dwi Yuniar; Mahundingan, Rosari O.; Rukmini, Rukmini; Andriani, Dewi (PPM STIKES Adi Husada, 2023)
Introduction &; Aim: Hypertension is a chronic disease, where the sufferer will have an impact on the emergence of health problems, one of which is psychological problems. Patients who have to take medicine daily sometimes experience boredom, sadness, and fear of complications. This activity aims to provide health education and practice Benson's relaxation techniques. Method of Activity: Before the action is carried out, counseling is conducted, namely conducting an initial survey, followed by a time and place contract and then implementation. The media used is a booklet containing hypertension and Benson's relaxation techniques. The methods were lectures, question and answer discussions, and demonstrations and provided Geriatric Depression Scale (GDS) questionnaires. Results: Activities were carried out in the RW 4 Kapasan Village and Simokerti Districts obtained 22 elderly people affected by hypertension. The results of depression screening found mild depression in 12 people (55%) before the action and 9 people (41%) with mild depression after the procedure. Likewise, the categorization of stage 1 hypertension was 14 people (64%), and after action 12 people (54.5%). Discussion: Changes experienced by the elderly Benson's relaxation technique can be an alternative as an action to manage blood pressure and psychological elderly with hypertension. This technique is effortless to do independently and can be done on the sidelines.